2015
DOI: 10.5688/ajpe79222
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students’ Preference for Using Mobile Devices in a Clinical Setting for Practice-Related Tasks

Abstract: Objective. To examine pharmacy students' ownership of, use of, and preference for using a mobile device in a practice setting. Methods. Eighty-one pharmacy students were recruited and completed a pretest that collected information about their demographics and mobile devices and also had them rank the iPhone, iPad mini, and iPad for preferred use in a pharmacy practice setting. Students used the 3 devices to perform pharmacy practice-related tasks and then completed a posttest to again rank the devices for pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Yet, students' representative associations participating in our study still reported a preponderance of lecture-based over practice-based learning while referring to problem-based and practicebased learning as their preferred education method in clinical pharmacy. The referred to preferred teaching methods are often linked to the use of digital technologies as enablers of more interactive approaches for learning that oppose the traditional passive lecture and involve students more in the clinical process (Richard, Hastings & Bryant, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, students' representative associations participating in our study still reported a preponderance of lecture-based over practice-based learning while referring to problem-based and practicebased learning as their preferred education method in clinical pharmacy. The referred to preferred teaching methods are often linked to the use of digital technologies as enablers of more interactive approaches for learning that oppose the traditional passive lecture and involve students more in the clinical process (Richard, Hastings & Bryant, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Health care providers are relying increasingly on DI databases in the form of applications on mobile devices to assist with clinical decision-making as smartphone adoption becomes more ubiquitous [12][13][14]. These databases are considered useful by many as they provide DI, including ADR information, at the point of care [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of pharmacy students examined their actual preferences when provided with three different sizes of device for use in answering clinical questions. The students overwhelmingly preferred the iPad mini over iPads or iPhones, as it provides a nice balance of size, weight, and screen size [17].…”
Section: Introductionmentioning
confidence: 99%